(untitled) (Journal of Chittagong Medical College Teachers’ Association, 2020)
Southeast part of the country resides more than 35 million people and Chattogram Medical College Hospital is the center hub for trauma management of this region. Trauma includes industrial injury as well as road traffic accident along with electric burn. Plastic Surgery department deals with this trauma patient for soft tissue coverage. The study shown four electric burn and one cancer patients having flap surgery for their wound coverage. In this study patients selected randomly over a period of one year. Wound at different part of body including head, neck, palm, hand, axilla and heel. We gave five different flaps to cover trauma and cancer defect. Wounds like various trauma including electric burns, cancer and snake bite. Snake bites are common in this hilly terrain. Cancer like SCC and malignant melanoma is also common in the long marine shore of Bay of Bengal. Flap maintain form and function of affected part which improves quality of life. Most of patients are young teenage, only two are elderly. About six months follow up flapsshow, are in good functionaland cosmetic outcome with no residual morbidity. All patients undergonea rehabilitation procedure to normal life. JCMCTA 2019 ; 30 (2) : 102-108